Building Evidence in Early Childhood Special Education: A Systematic Review of Replication Intervention Studies. (February 2018) - Banerjee, Rashida; Movahedazarhouligh, Sara; Millen, Kaitlyn; Luckner, John L.
Valid and evidence-informed practices are critical to help young children with disabilities and their families with highly effective interventions and instruction to reach their potentials. Replication research is critical for appraising research and identifying evidence-based practices. The purpose of this study was to replicate the methods used by Cook and colleagues and conduct a systematic review of the quantity, type, and findings of replication research in early childhood special education (ECSE). An intervention study was considered a replication if (a) the stated purpose of the study was to replicate, expand, further investigate, or use a previously conducted study as its basis and (b) the findings of the study were compared with the results of previous studies. Two hundred ninety-seven published articles in three journals relevant to ECSE from 2012 to 2016 were reviewed to identify intervention studies. From the 78 identified intervention studies, we found 44 studies (56%) that met the criteria for replication. Author overlap occurred for 20 studies out of the 44 replication studies (46%). Our investigation revealed that ECSE journals published a significantly larger number of replication studies (56%) than those reported by Cook and colleagues (31%); however, the scarce number of direct replication was concerning. We recommend intentional and proactive steps be taken to promote and value replication research in ECSE.